PENAMBAHAN CONTRAX RELAX STRETCHING LEBIH EFEKTIF DARIPADA BALLISTIC STRETCHING PADA LATIHAN DEPTH JUMP TERHADAP PENINGKATAN VERTICAL JUMP ATLET BASKET SMA (SLUA) SARASWATI 1 DENPASAR - A.A.Istri Firasti Widyaratni; Nila Wahyuni; I Made Muliarta; I Putu Sutha Nurmawan (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2016)
ABSTRACTVertical jump is the highest jump movement focusing leg muscle strength to achieve a stepping straight up to the maximum. The basic technique is predominantly done in the game of basketball, especially when doing the shooting, where players have to jump shoot to put the ball into the ring. The purpose of this study was to determine the effect of the interpolation of contrax relax stretching is more effective in increasing vertical jump than ballistic stretching on depth jump exercise. The research result showed, there is an increase of vertical jump in the group one (ballistic stretching) of 4.55 whereas in the group two (contrax relax stretching) there was an increase of 8.36. Paired t-test result showed the significant result with p=0.000 (p<0.05) in the group one and p=0.000 (p<0.05) in the group two.Independent t-test result showed a significant difference in the vertical jump between the group one and group two, where p=0.000 (p<0.05). Based on these results it can be concluded that the addition of contrax relax stretching is more effective in increasing vertical jump than ballistic stretching on depth jump exercise. Keywords : Vertical jump, contrax relax stretching, ballistic stretching, depth jump